Origami Theory and its Applications: A Literature Review - Fei, L.J.; Sujan, Debnath (School of Engineering & Science, Curtin University Sarawak Campus, 2012)
This paper presents the fundamentals of Origami engineering and its application in nowadays as well as future industry. Several main cores of mathematical approaches such as Huzita-Hatori axioms, Maekawa and Kawasaki's theorems are introduced briefly. Meanwhile flaps and circle packing by Robert Lang is explained to make understood the underlying principles in designing crease pattern. Rigid origami and its corrugation patterns which are potentially applicable for creating transformable or temporary spaces is discussed to show the transition of origami from paper to thick material. Moreover, some innovative applications of origami such as eyeglass, origami stent and high tech origami based on mentioned theories and principles are showcased in section III; while some updated origami technology such as Vacuumatics, self-folding of polymer sheets and programmable matter folding which could greatly enhance origami structure are demonstrated in Section IV to offer more insight in future origami.